Italy through the red lens Italian politics and society in communist propaganda films (1946–79) - Fantoni, Gianluca (Italian and Italian American Studies, 2021)
Intro -- Acknowledgements -- Contents -- List of Images -- Chapter 1: Introduction -- Bibliography -- Part I: The Italian Communist Party between Socialist Realism and Neorealism (1944-1956) -- Chapter 2: Togliatti's Partito nuovo and Italian Cinema -- Bibliography -- Chapter 3: Socialist Realism Italian-Style: PCI Cinematic Propaganda in the Stalin Era -- Bibliography -- Part II: Dealing with the Modern (1956-1970) -- Chapter 4: Peace and Sputnik, the Boom, and Television (1956-1964) -- Bibliography -- Chapter 5: The First Years of Unitelefilm and the PCI After Togliatti (1964-1967) -- Bibliography -- Chapter 6: The Workers, the Students, and the Election Campaign of 1968 -- Bibliography -- Chapter 7: The Lice and the Whale: Filmmakers, Militant Cinema, and the Italian Communist Party -- Bibliography -- Part III: A Decade of Living Dangerously: The Turbulent Peak (and the Seeds of Decline) of the Italian Communist Party (1970-1979) -- Chapter 8: The Early 1970s: Unitelefilm, the Fascist Threat, and the 'Historic Compromise' -- Bibliography -- Chapter 9: Hegemony Within Reach (1974-1976) -- Bibliography -- Chapter 10: Women's Issues, Feminism, and the PCI -- Bibliography -- Chapter 11: Hegemony Fades Away (1977-1979) -- Bibliography -- Chapter 12: Conclusion -- Bibliography -- Film Index -- Subject Index.